Environmental Social Governance (ESG) Framework for Public Private Partnership (PPP) in Indonesia - Yuki Mahardhito Adhitya Wardhana (Institut Teknologi Sepuluh Nopember (ITS), 2024)
Environmental and social risks are risks that can disrupt the sustainability of infrastructure provision through the PPP scheme. PPP is a cooperation scheme involving many stakeholders and each stakeholder can be part of mitigating risks, including environmental risks. Environmental risk mitigation can be carried out through instruments and frameworks owned by each stakeholder. This research aims to map the ESG framework that exists in PPP schemes in Indonesia based on existing instruments for stakeholders to be able to make ESG an effective instrument for mitigating environmental and social risks. The research method used in this research is qualitative because the analysis used in this research is a descriptive and in-depth observation of the PPP ecosystem in Indonesia. The results of this research show that there are eight stakeholders in PPP in Indonesia. Each stakeholder has an instrument and can apply the ESG framework based on the instrument they have. Implementing the ESG framework can mitigate environmental and social risks in business processes carried out by stakeholders in the PPP ecosystem in Indonesia.